Disclosures of Information About a Business Combination in the Context of the Assessment of its Economic Characteristics - Janowicz , Magdalena (Studia Oeconomica Posnaniensia, 2016)
Taking into consideration the nature and characteristics of a particular transaction, a different scope of disclosures might be required for different types of a business combination, depending on the accounting regulations used. The author outlined the complexity of the term "business combinations" and the main aspects that have the greatest effect on the information presented in a financial statement. The theoretical part was complemented with a case study. The methodology used involves analysis of literal sources and legal regulations, case study and content analysis.